Subtle Linguistic Cues Affect Children's Motivation - Cimpian, Andrei; Arce, Holly-Marie C.; Markman, Ellen M.; Dweck, Carol S. (Psychological Science, 2007)
Are preschoolers’ reactions to setbacks influenced by whether their successes are rewarded with generic or nongeneric praise? Previous research has focused on the role of category-referring generics (e.g., ‘‘Dogs are friendly’’) in shaping children’s knowledge about natural kinds (see Gelman, 2004). Generic sentences can, however, refer to individuals as well as categories. For example, ‘‘John is friendly’’ is generic because it reports a general regularity—albeit about a single person—rather than a particular fact or episode (Carlson & Pelletier, 1995). In contrast, the nongeneric ‘‘John was friendly at the party’’ refers to a specific past event. Generic sentences about an individual imply that the particular behavior commented on (e.g., John smiling warmly) stems from a stable trait (e.g., friendliness) or skill (see Gelman & Heyman, 1999). Are children sensitive to this subtle connotation with respect to their own behavior? If so, then generic praise may lead children to think in trait terms, such that later mistakes could signal a negative trait or low ability and therefore undermine motivation (Dweck, 1999, 2006). Preliminary support for this claim comes from a study by Kamins and Dweck (1999). Praising the whole person (e.g., ‘‘You are a good boy/girl’’) after success on a task fostered helpless responses to subsequent mistakes more than praising the process through which success was achieved (e.g., ‘‘You found a good way to do it’’). We suggest that children’s behavior was in part driven by the fact that the person praise was generic, connoting a stable trait of the child, while the process praise was nongeneric, focusing on one specific episode. Would manipulating only the genericness of the praise result in similar patterns of coping? For example, would children’s motivation be affected differently by ‘‘You are a good drawer’’ (generic) than by ‘‘You did a good job drawing’’ (nongeneric)? Note that these sentences are much more similar than the person-process pairs used by Kamins and Dweck—so similar, in fact, that adults may not be aware of their contrasting implications and are thus likely to use them interchangeably in interactions with children. Demonstrating that children praised in these two ways react differently to a challenge would be evidence for the importance of the generic/nongeneric distinction in shaping young children’s conceptions of their abilities.